“Gestión de riesgos Mayores en las instalaciones de la dirección Distrital Centro Oriental de tierras y reforma agraria del MAGAP: Plan de Emergencia” - Paguay Gusque, Klever Iván (2016)
The present study has taken into account those activities where the importance of risk management is highlighted, the major risks in each of the four areas of the institution have been identified, analyzed and evaluated and for this purpose it is sought to reduce and prevent Emergencies. The Central Eastern District Land and Agrarian Reform Directorate of MAGAP as the lead institution responsible for the distribution, redistribution, regrouping, legalization and use of land integrated into productive plans for a sustainable use of the land resource and the improvement of agrarian reform, Must consider that because of its geographical location is exposed to risks such as earthquakes and volcanic eruptions. In this sense, the study includes an observation of the characteristics of possible risk situations, to identify the different ways of facing them; Therefore the present investigation has taken into account the methods of evaluation of the Secretariat of Risk Management and also with international methodologies such as: MESERI, NFPA, among others that will be implemented in each of the areas A1-Ground floor, A2-Piso 1, A3-Piso 2 and A4-Ground floor external block to be analyzed, obtaining results that will allow establishing preventive measures where they present greater risk, especially to ensure the integrity of workers.